Positive Response to One-Year Treatment With Burosumab in Pediatric Patients With X-Linked Hypophosphatemia - Martín Ramos, Silvia; Gil-Calvo, Marta; Roldán, Virginia; Castellano Martínez, Ana; Santos, Fernando (Frontiers in Pediatrics, 2020)
X-linked hypophosphatemia (XLH) causes significant burden in pediatric patients in spite of maintained treatment with phosphate supplements and vitamin D derivatives. Administration of burosumab has shown promising results in clinical trial but studies assessing its effect in the everyday practice are missing. With this aim, we analyzed the response to one-year treatment with burosumab, injected subcutaneously at 0.8 mg/kg every 2 weeks, in 5 children (3 females) aged from 6 to 16 years, with genetically confirmed XLH. Patients were being treated with phosphate and vitamin D analogs until the beginning of burosumab treatment. In all children, burosumab administration led to normalization of serum phosphate in association with marked increase of tubular reabsorption of phosphate and reduction of elevated serum alkaline phosphatase levels. Baseline height of patients, from -4.51 to -0.87 SD, increased in the three prepubertal children (+0.84, +0.89 and +0.16 SD) during burosumab treatment. Growth improvement was associated with reduction in body mass index (-1.75, -1.47 and -0.17 SD, respectively), suggesting a salutary effect of burosumab on physical activity and body composition. Burosumab was well tolerated, mild local pain at the injection site and transient and mild headache following the initial doses of burosumab being the only reported undesirable side effects. No patient exhibited hyperphosphatemia, progression of nephrocalcinosis, worsening of metabolic control or developed hyperparathyroidism. Mild elevation of serum PTH present at the beginning of treatment in one patient 4 was not modified by burosumab administration. These results indicate that in the clinical setting, beyond the strict conditions and follow-up of clinical trials, burosumab treatment for one year exerts positive effects in pediatric patients with XLH without major adverse events.